Influence of APOE Gene Polymorphism on Interindividual and Interethnic Warfarin Dosage Requirement: A Systematic Review and Meta‐Analysis. Issue 5 (October 2016) - Yu, Wan‐ying; Sun, Xue; Wadelius, Mia; Huang, Lihua; Peng, Chen; Ma, Wan‐le; Yang, Guo‐Ping
Summary: Background: Warfarin is the most extensively used coumarin anticoagulant. It has been shown that the anticoagulant effect of warfarin is associated with genetic variation. Apolipoprotein E (ApoE) is a possible candidate to influence the maintenance dose of warfarin. ApoE affects the vitamin K cycle by mediating the uptake of vitamin K into the liver. The vitamin K cycle is the drug target of warfarin. However, the association between genetic variants of the APOE gene and warfarin dose requirement is still controversial. Methods: Revman 5.3 software was used to analyze the relationship between APOE genotypes and warfarin dose requirements. Results: In our meta‐analysis, the E2/E2 genotype was significantly associated with warfarin dose. E2/E2 patients required 12% ( P = 0.0002) lower mean daily warfarin dose than E3/E3 carriers. In addition, subgroup analysis showed that Asians with the E4/E4 genotype tended to need lower warfarin maintenance doses, while the African American E4/E4 carriers needed slightly higher doses than E3/E3 carriers; however, these subgroups were very small. Conclusion: This is the first meta‐analysis of the association between APOE genotypes and warfarin dose. APOE E2/E2 might be one of the factors affecting warfarin dose requirements. The effect of APOE may vary between ethnicities.